2021
DOI: 10.31234/osf.io/ys8jr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Usual Suspects: How psychological motives and thinking styles predict the endorsement of well-known and COVID-19 conspiracy beliefs

Abstract: Research on belief in conspiracy theories identified many predictors, but often failed to investigate them together. In the present study, we tested how the most important predictors of beliefs in conspiracy theories explain endorsing COVID-19 and non-COVID-19 conspiracy theories, and conspiracy mentality. Apart from these three measures of conspiratorial thinking, participants (N = 354) completed several measures of epistemic, existential, and social psychological motives, as well as cognitive processing vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…International opinion polls suggest that conspiracy theory (CT) beliefs are now more widely adopted, and circulated across western countries than ever, with recent events such as the COVID‐19 protests and Capitol riots being strong outward manifestations of these belief systems (Depoux et al, 2020; Georgiou et al, 2020; Gligorić et al, 2021; O'Connell et al, 2021; Sallam, 2021; Uddin et al, 2021; YouGov‐Cambridge Globalism Project, 2020). Although CTs offer sometimes intriguing narratives of events (e.g., the JFK assassination by multiple actors), they are usually false and can lead to unjustified mistrust of authorities, rejection of vaccinations and harmful or hurtful rejection of crimes against humanity (Douglas et al, 2015; Georgiou et al, 2020; Jolley & Douglas, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International opinion polls suggest that conspiracy theory (CT) beliefs are now more widely adopted, and circulated across western countries than ever, with recent events such as the COVID‐19 protests and Capitol riots being strong outward manifestations of these belief systems (Depoux et al, 2020; Georgiou et al, 2020; Gligorić et al, 2021; O'Connell et al, 2021; Sallam, 2021; Uddin et al, 2021; YouGov‐Cambridge Globalism Project, 2020). Although CTs offer sometimes intriguing narratives of events (e.g., the JFK assassination by multiple actors), they are usually false and can lead to unjustified mistrust of authorities, rejection of vaccinations and harmful or hurtful rejection of crimes against humanity (Douglas et al, 2015; Georgiou et al, 2020; Jolley & Douglas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such worldviews allow people to maintain their beliefs over time rather than experience the distress of confronting disconfirmatory evidence. In addition, CT beliefs can also be a way to justify certain behaviours or reject official narratives that are inconsistent with broader views about government and the role of the authorities (e.g., contest the existence of the COVID‐19 virus), that confront rather complex topics (e.g., the diverse consequences of a complex health crisis, Douglas, 2021; Georgiou et al, 2020; Gligorić et al, 2021). Moreover, as Cichocka et al (2016) suggest, these CTs can allow a person to validate their beliefs and strengthen their sense of in‐group membership and thereby allow them to impute blame for negative outcomes to external parties (e.g., governing bodies) or expert figures of power (e.g., Bill Gates's role in the COVID‐19 pandemic response; Georgiou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, self-report measures on preference for intuitive versus analytical thinking showed that more intuitive and less analytical thinking styles were related to higher levels of COVID-19 conspiracy beliefs ( Alper et al, 2020 ; Erceg et al, 2020 ; Fuhrer and Cova, 2020 ; Gligorić et al, 2021 ; Kim and Kim, 2021 ; Lazarević et al, 2021 ). Individuals who tend to rely on their intuitions and who had lower basic scientific knowledge were moreover less able to distinguish between true and false information regarding COVID-19 and more likely to share misinformation ( Pennycook et al, 2020b ).…”
Section: Resultsmentioning
confidence: 98%
“…A person's tendency to believe in conspiracy theories may also be driven, in part, by their personality traits ( Bowes et al, 2020 ). People scoring high on the Dark Tetrad traits (e.g., Machiavellianism, narcissism, psychopathy, and sadism; Chabrol et al, 2009 ) are more likely to endorse COVID-19 conspiracy theories ( Gligorić et al, 2021 ; Hughes and Machan, 2021 ; Kay, 2020 , 2021b ; Malesza, 2021 ). This may be the result of a tendency of high-scorers to distrust others and suffer from delusions (e.g., believing that other people can read one's mind) ( Kay, 2021a , b ; Larsen et al, 2021 ; Meuer and Imhoff, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation